"Get fit!" – The use of imperatives in Australian English gym advertisements on Facebook. (April 2017) - Zjakic, Hana; Han, Chong; Liu, Xiangdong
Abstract: Advertisements aim to persuade individuals to purchase a product or service over the claims of competitors. With advances in technology in recent years, more advertisers are incorporating web advertising into their marketing strategies, often combining elements of both online and traditional modes of advertising to achieve their aim. As web advertising is a relatively new mode of communication, the present paper aims to explore the use of language in web advertising, using a collection of advertisements taken from the official Facebook pages of three gyms in Australia. Our focus is on imperatives which have been identified as a typical feature of advertising discourse. We provide a multi-modal analysis of Facebook advertisements by focusing on the role of imperatives in text and the interplay between text and image. Imperatives are often considered to be threatening to an individual׳s negative face as they express the directive force associated with commands and requests. Therefore, the present study aims to identify the dominant discourse function of imperatives in Facebook gym advertisements. Adopting the theoretical frameworks on politeness (Brown and Levinson, 1987; Locher and Watts, 2006;Park, 2008a, 2008b ) and impoliteness (Haugh, 2010a ; Haugh and Bousfield, 2012), we argue that while imperatives may occasion linguistic manifestation of impoliteness in their surface value, imperatives in web advertising are rather a strategy used by advertisers to create a sense of familiarity between the advertiser and receiver which is further emphasised through the advertiser׳s use of visual elements (such as image and video). The data is first categorised into two groups based on whether or not the advertisements contain imperative verbs. Using the discourse classification of imperatives byPennock-Speck and Fuster-Márquez (2014), the advertisements containing imperative verbs are then categorised based on their discourse functions. Our findings suggest that imperatives in Facebook gym advertisements are used instead to capture the attention of Facebook users and inform them about the product or service. Furthermore, imperatives in Facebook advertisements typically occur in onset position and are accompanied by visual elements such as still images or videos. Thus, it can be argued that rather than threatening the addressee׳s negative face, Facebook advertisers focus more on appealing to their audience so as to increase the number of potential customers that are interested in what their business has to offer. The findings provide a basis for future studies on imperatives in web advertising and contribute to the understanding of im/politeness in online communication. Highlights: Imperatives are used to inform Facebook users about the product or service. Imperatives create a sense of familiarity between the advertiser and receiver. Imperatives typically occur in onset position and are accompanied by visual elements. Whether imperatives are evaluated as impolite depends on urgency, context and power.